Journal of Industrial Engineering International - Rashidi, Alireza
Journal of Industrial Engineering International is an international journal dedicated to the latest advancement of industrial engineering. The goal of this journal is to provide a platform for engineers and academicians all over the world to promote, share, and discuss various new issues and developments in different areas of industrial engineering. All manuscripts must be prepared in English and are subject to a rigorous and fair peer-review process. Accepted articles will immediately appear online. The journal publishes original research articles, review articles, technical notes, case studies and letters to the Editor, including but not limited to the following fields: Operations Research and Decision-Making Models Production Planning and Inventory Control Supply Chain Management Quality Engineering Applications of Fuzzy Theory in Industrial Engineering Applications of Stochastic Models in Industrial Engineering Applications of Metaheuristic Methods in Industrial Engineering.